2013
DOI: 10.1007/s11434-013-5669-6
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent studies on coronal dynamics: Streamers, coronal mass ejections, and their interactions

Abstract: In this article I present a review of recent studies on coronal dynamics, including research progresses on the physics of coronal streamers that are the largest structure in the corona, physics of coronal mass ejections (CMEs) that may cause a global disturbance to the corona, as well as physics of CME-streamer interactions. The following topics will be discussed in depth: (1) acceleration of the slow wind flowing around the streamer considering the effect of magnetic flux tube curvature; (2) physical mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 167 publications
(283 reference statements)
0
11
0
Order By: Relevance
“…It is a core issue of CME studies regarding the release mechanism of magnetic energy in the corona. Two major mechanisms have been suggested including the ideal MHD flux rope instability and magnetic reconnection (see, e.g., Chen et al, 2007aChen et al, , 2007bChen 2013). It is possible that in a specific event both processes contribute.…”
Section: Discussionmentioning
confidence: 99%
“…It is a core issue of CME studies regarding the release mechanism of magnetic energy in the corona. Two major mechanisms have been suggested including the ideal MHD flux rope instability and magnetic reconnection (see, e.g., Chen et al, 2007aChen et al, , 2007bChen 2013). It is possible that in a specific event both processes contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Coronal Mass Ejections (CMEs) are observed to be closely related to and frequently interact with helmet streamers (e.g., Howard et al 1985;Hundhausen 1993;McAllister & Hundhausen 1996;Chen et al 2010Chen et al , 2011Feng et al 2011;Chen 2013). In the streamer region, the Alfvénic speed is lower than that of the surroundings because of a much higher plasma density, and the plasma outflow is slow and hardly measurable in the closed magnetic field region (Habbal et al 1997;Strachan et al 2002;Kwon et al 2013;Chen 2013). Due to these special plasma and magnetic conditions, the streamer structure is expected to facilitate the formation and/or enhancement of a CME-driven shock.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it is expected that when a CME disturbance propagates into a dense coronal structure with low Alfvénic speed, the disturbance may steepen into a shock, or a preexisting shock may get enhanced in strength, also favoring electron acceleration. Thirdly, it is suggested that the closed field topology within the streamer, when swept by an outward-propagating shock, may give rise to a collapsing magnetic trap configuration (Baker et al 1987;Zlobec et al 1993;Somov & Kosugi 1997;Chen 2013), within which electrons are trapped by the upstream field lines, and may return to the shock and be accelerated repeatedly. This also favors the generation of energetic electrons.…”
Section: Conclusion and Discussionmentioning
confidence: 99%